1997
DOI: 10.1002/j.2161-0045.1997.tb00998.x
|View full text |Cite
|
Sign up to set email alerts
|

Annual Review: Practice and Research in Career Counseling and Development—1996

Abstract: The National Career Development Association's (NCDA) Professional Standards Committee (1997) has recently identified 11 competency areas (career development theory, individual and group counseling skills, individual and group assessment, information resources, and program management and implementation, consultation, diverse populations, supervision, ethical legal issues, and research evaluation, and technology). These competencies were used as categories for classifying research on career development and couns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 96 publications
(1 reference statement)
0
15
0
1
Order By: Relevance
“…The focus has shifted from the individual and age-appropriateness, to the interaction between organism and environment, or person and context (Niles, 1997(Niles, , 1998Raskin, 1998;Séhrnitt-Roderrnund & Silbereisen, 1998;Stead, 1996;Vondracek & Reitzle, 1998). Hall (1992) promoted the use of a broad theoretical frame in which the complexity and growth aspects of career decision-making are accommodated.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…The focus has shifted from the individual and age-appropriateness, to the interaction between organism and environment, or person and context (Niles, 1997(Niles, , 1998Raskin, 1998;Séhrnitt-Roderrnund & Silbereisen, 1998;Stead, 1996;Vondracek & Reitzle, 1998). Hall (1992) promoted the use of a broad theoretical frame in which the complexity and growth aspects of career decision-making are accommodated.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…He suggested that the theory of Super would provide such a frame. Super's concept of career stages has had a major influence on career assessment and counselling (Richman, 1993), and his contribution represents an unparalleled legacy in developmental career theory (Isaacson & Brown, 1997;Niles, 1997). Super's Life-Span Life-Space Theory focuses on career development in preference to the concept of occupational choice, advocated by Holland (Super, 1980).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Segundo Niles (1997), a informação de carreira 2 pode ajudar os clientes a tomar decisões, entretanto, os orientadores devem se certificar de que as mesmas sejam precisas, relevantes e recentes, de modo a aumentar a probabilidade dos clientes obterem informação adequada sobre as carreiras, encorajando-os a usar fontes múltiplas de informação. Como salienta Brown (2003), cada jovem tem necessidades únicas.…”
Section: Introductionunclassified